Diabetic foot syndrome as an interdisciplinary problem - Emilia Rymkiewicz; Katarzyna Joanna Sołdaj-Bukszyńska; Marcin Kowalik; Beata Lis; Grzegorz Dzida (Kazimierz Wielki University, 2017)
Diabetes is a metabolic disease of the growing maturity. Diabetic foot syndrome is a chronic complications of diabetes. In neuropathic sensory disorders, ischemia of the lower limbs, and improper alignment metabolic control may occur in minor injuries around the foot, giving rise to a difficult healing ulcers. Even minor wounds rapidly infection by pathogenic bacteria, which significantly hinders their treatment. Health and life-saving solution in situations of persistent symptoms of infection is amputation of the lower limb. Doing so, however, does not solve the problem of diabetic and should be the final proceedings after having exhausted all possible treatments for diabetic foot syndrome.